A Prospective Study of Azilsartan Medoxomil in the Treatment of Patients with Essential Hypertension and Type 2 Diabetes in Asia. (7th January 2022) - Deerochanawong, Chaicharn; Chang, Kuan-Cheng; Woo, Yu Cho; Lai, Wen-Ter; Chutinet, Aurauma
Abstract : This phase 4 study evaluated the efficacy and safety of azilsartan medoxomil (AZL-M) in patients with essential hypertension and type 2 diabetes mellitus (T2DM) in Hong Kong, Taiwan, and Thailand. This was a prospective, multicenter, single-arm, open-label study with patients aged 18–75 years with T2DM and essential hypertension and on stable treatment for T2DM. Patients with uncontrolled hypertension were treated with AZL-M 40 mg daily, with the option to uptitrate to 80 mg at 6 weeks. In all, 380 of the 478 patients screened in Hong Kong, Taiwan, and Thailand were enrolled. At week 6, 97 patients (25.5%) were titrated up to AZL-M 80 mg based on BP readings. At 12 weeks, 54.8% of patients reached the blood pressure (BP) goal of <140/85 mm Hg by trough sitting clinic BP (primary endpoint), and 62.8% and 27.0% achieved a BP of <140/90 mm Hg and <130/80 mm Hg, respectively. The efficacy of AZL-M over 12 weeks was also seen in different age and body mass index groups. The incidence of treatment emergent adverse events (TEAEs) was 12.9% before 6 weeks and 16.1% after 6 weeks, and they were mostly mild in severity. The most frequent TEAE was dizziness (4.7%). The incidence of TEAEs leading to study drug discontinuation (4.5%) and drug-related TEAEs (5.0% before 6 weeks; 3.9% after 6 weeks) was low. In patients with essential hypertension and T2DM in Asia, treatment with AZL-M indicated a favorable efficacy and safety profile in achieving target BP.